Higher Education Instructors’ Usage of and Learning From Student Evaluations of Teaching – Do Achievement Goals Matter? - Hein, Julia; Janke, Stefan; Rinas, Raven; Daumiller, Martin; Dresel, Markus; Dickhäuser, Oliver (Frontiers in Psychology, 2021)
Identifying what motivates and hinders higher education instructors in their self-regulated learning from student evaluations of teaching (SETs) is important for improving future teaching and facilitating student learning. According to models of self-regulated learning, we propose a model for the usage of SETs as a learning situation. In a longitudinal study, we investigate the associations between achievement goals and the usage of and learning from SETs in the context of higher education. In total, 407 higher education instructors (46.4% female; 38.60 years on average) with teaching commitments in Germany or Austria reported their achievement goals in an online survey. Out of these participants, 152 instructors voluntarily conducted SET(s) and subsequently reported their intentions to act on the feedback and improve future teaching in a short survey. Using structural equation modeling, we found, in line with our hypotheses, that learning avoidance, appearance approach, and appearance avoidance goals predicted whether instructors voluntarily conducted SET(s). As expected, learning approach and (avoidance) goals were positively associated with intentions to act on received SET-results and improve future teaching. These findings support our hypotheses, are in line with assumptions of self-regulated learning models, and highlight the importance of achievement goals for instructors’ voluntary usage of and intended learning from SET(s). To facilitate instructors’ learning from SET-results, our study constitutes a first step for future intervention studies to build on. Future researchers and practitioners might support instructors’ professional learning by encouraging them to reflect on their SET-results.